The effect of weight reduction and nutritional intervention on athletic performance in female weightlifters - Pang, J.; Jiao, Y.; Zhang, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The purpose of this study was to investigate the effect of nutritional intervention on athletic performance in weightlifters. Participants were undergoing either gradual bodyweight reduction or rapid bodyweight reduction, in order to improve performance after the weight loss. Methods Twelve female weightlifters were divided randomly into two groups consisting of an experimental group and a control group. The athletes in both groups were trained at the same intensity and supplied with the same diet. However, the subjects in the experimental group were also supplied with nutrientenriched food, including weight-loss bars, vitamins and electrolytes both during weight reduction and after the weight-loss. Alternatively those in the control group were supplied with the placebo. Aerobic and anaerobic capability of the subjects in both groups was tested before and after weight-loss. Results The body mass of the experimental group and control group decreased from 67.4±14.2kg to 64.6±14.1kg and from 67.4±15.5kg to 64.3±15.4kg, respectively. In the recovery period after the rapid weight reduction, the blood lactate concentration, heart rate and neural fatigue grade of the experiment group decreased significantly compared to the control group. In the Wingate anaerobic test, there was no significant difference in the peak power per body weight, mean power and minimal power during chronic weight-loss, rapid weight-loss and the recovery phase. However, the peak power per body weight of the experiment group was much higher than the basic value in the first day (P1) and the third day (P3) after the rapid weight-loss. Conclusions The controlled, restricted energy intake caused body weight loss in both groups. The combined supplementation of additional vitamins and electrolytes could help improve sports performance by maintaining aerobic and anaerobic capabilities of weightlifters.